PENGARUH KOMPETENSI, MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA LUBUKLINGGAU - Betti Nuraini; Sri Ayu Lestari (Jurnal Interprof, 2020)
The method used is a questionnaire method of four variable items, namely Competency, Motivation, Organizational Culture and Employee Performance. The number of samples was 63 respondents. Data analysis used is descriptive quantitative by using SPSS application. The first hypothesis test results,is the Competency variable (X1) has a partially significant effect on Employee Performance (Y) in the Lubuklinggau City Department of Trade and Industry. The second hypothesis test results is, the Motivation variable (X2) has a partially significant effect on Employee Performance (Y) in the Lubuklinggau City Trade and Industry Office. The third hypothesis test results is, the variable Organizational Culture (X3) has a partially significant effect on Employee Performance (Y) in the Lubuklinggau City Trade and Industry Office. The fourth hypothesis test results is show that, the independent variable Competence and Motivation has a significant simultaneous effect on the dependent variable Employee Performance in the Lubuklinggau City Trade and Industry Office. The fifth hypothesis test results is show that, the independent variable Competency and Organizational Culture has a significant influence simultaneously on the dependent variable Employee Performance in the Lubuklinggau City Trade and Industry Office. The sixth hypothesis test results show that, the independent variable of Motivation and Organizational Culture has a significant influence simultaneously on the dependent variable Employee Performance in the Trade and Industry Office of Lubuklinggau City. The results of the seventh hypothesis test variables show that, the independent variables Competency, Motivation, and Organizational Culture have a significant influence simultaneously on the dependent variable Employee Performance in the Lubuklinggau City Trade and Industry Office.